Colorimetric High‐Throughput Screening Method for Directed Evolution of Prazole Sulfide Monooxygenase. (28th June 2022) - Liu, Feng; Geng, Qiang; Zhao, Chen; Ren, Shi‐Miao; Yu, Hui‐Lei; Xu, Jian‐He
Abstract: Baeyer‐Villiger monooxygenases (BVMOs) are important biocatalysts for the enzymatic synthesis of chiral sulfoxides, including chiral sulfoxide‐type proton pump inhibitors for the treatment of gastrointestinal diseases. However, native BVMOs are not yet suitable for practical application due to their unsatisfactory activity and thermostability. Although protein engineering approaches can help address these issues, few feasible high‐throughput methods are available for the engineering of such enzymes. Herein, a colorimetric detection method to distinguish sulfoxides from sulfides and sulfones was developed for prazole sulfide monooxygenases. Directed evolution enabled by this method has identified a prazole sulfide monooxygenase Cb BVMO variant with improved activity and thermostability that catalyzes the asymmetric oxidation of lansoprazole sulfide. A 71.3 % increase in conversion and 6 °C enhancement in the melting point were achieved compared with the wild‐type enzyme. This new method is feasible for high‐throughput screening of prazole sulfide monooxygenase variants with improved activity, thermostability, and/or substrate specificity. Abstract : A colorimetric high‐throughput screening method for the rapid screening of desired variants with improved activity, thermostability, and/or substrate specificity was developed based on distinguishing sulfoxides from sulfides and sulfones. Using this method, a Cb BVMO variant was identified with improved activity and thermostability, and a 71.3 % increase in catalyzing the asymmetric oxidation of lansoprazole sulfide.